WAX ESTERS PRODUCTION BY ALCOHOLYSIS OF PALM OIL FRACTIONS - Erin Ryantin Gunawan; Dedy Suhendra (Universitas Gadjah Mada, 2008)
The lipase synthesis of wax esters using palm oil fractions (palm oil and palm kernel oil) and long chain alcohol as substrates was carried out. The present work focuses on the synthesis of wax esters using Lipozyme. Five parameters such as reaction time, temperature, amount of enzyme, molar ratio of substrates and various organic solvents of the reaction system were investigated. The optimum yields were achieved at the reaction temperature of 40 - 50 °C for palm oil (PO) and 40 °C for palm kernel oil (PKO) alcoholysis, a reaction time of 5 - 7 h for PO and 7 - 10 h for PKO alcoholysis, 0.15 g of enzyme for both PO and PKO alcoholysis, molar ratio at 3:1 (alcohol: PO or PKO), and the best solvent for the reactions was hexane. Percentage yields of esters obtained at these optimum reaction conditions was 83% refined, bleached and deodorized (RBD) palm oil alkoholysis and 87% for RBD palm kernel oil alcoholysis respectively